The Influence of Employment Stress On the Academic Performance of Working Students: Perspectives from Pakistan - Hassan, Mehreen; Hassan, Waseem; Sadat, Mojawir Ahmad; Jehan, Noor; Habib, Nargis; Murtaza, Ghulam (International Journal of Engineering and Management Sciences, 2024)
One must grasp stress's intricacy to develop and implement stress-reduction strategies. Employment-related stress on academic performance is becoming an acute concern for psychological and mental health in Pakistan. The current research focuses on how employment-related stress interferes with graduate students' academic performance in Parachinar, District Kurram Khyber Pakhtunkhwa, Pakistan. This investigation applies quantitative methods—the Govt. Postgraduate College Parachinar, District Kurram, Khyber Pakhtunkhwa Pakistan, completed a standardized questionnaire to 180 students from various academic disciplines.The findings illuminate stress's intricacy. It may be utilized to establish and encourage more efficient and achievable strategies or techniques that improve academics and job satisfaction, inspiration, and effectiveness at the individual and organizational levels.The research study concluded that 81.67% of male students suffered from employment stress. Student stressors include workload (31.67%), lack of time management (9.44%), interpersonal conflicts (20.00%), high study load (21.11%), and financial problems (17.78%), and the coping strategies being adopted by these students; Moral support (13.89%), Social support (30.00%), Financial support (45.00%), and Job enrichment (11.11%). The research concludes that addressing the highlighted concerns, counselling, and other successful coping strategies may alleviate academic and employment stress.